The Effect of Silver Oxide on the Structural and Optical Properties of ZnO: AgO Thin Films - Abbas, Hawraa H.; Hasan, Bushra A. (Iraqi Journal of Science, 2022)
Compounds from ZnO doped with AgO in different ratio (0,3,5,7, and 9)wt.% were prepared.Thin films from the prepared compounds were deposited on a glass substrate using the pulsed laser deposition method. The XRD pattern confirmed the presence of a single-phase hexagonal wurtzite ZnO structure, without the presence of a secondary phase. AFM measurements showed an increase in both average grain size and average surface roughness with increasing concentration content of (AgO).The crystallite size of ZnO of the main peak corresponding to the preferred plane of crystal growth named (100) increases from 17.8 to 22.5nm by increasing of AgO doping ratio  from 0 to 9%. The absorbance and transmittance in the wavelength range (350-1100 nm) were used to determine the optical properties. The results showed that the optical energy gap for direct allowed transition (r =0.5 )are (3.21, 3.2,3.15, 3.15, 2.95 ) Ev, respectively. The optical constants were also measured as a function of wavelength. This optical measurements  showed  the prepared thin film have many applications for solar cell fabrication  and sensing  devices.